Carboxylesterase catalyzed 18O-labeling of carboxylic acid and its potential application in LC-MS/MS based quantification of drug metabolites. Issue 5 (October 2019) - Yu, Zaikuan J.; Roesner, Joseph M.; Lutz, Ryan; Liang, Yuexia; Baker, James; Smith, Dustin M.; Fan, Peter W.
Abstract: LC-MS quantification of drug metabolites is sometimes impeded by the availability of internal standards that often requires customized synthesis and/or extensive purification. Although isotopically labeled internal standards are considered ideal for LC-MS/MS based quantification, de novo synthesis using costly isotope-enriched starting materials makes it impractical for early stage of drug discovery. Therefore, quick access to these isotope-enriched compounds without chemical derivatization and purification will greatly facilitate LC-MS/MS based quantification. Herein, we report a novel 18 O-labeling technique using metabolizing enzyme carboxylesterase (CES) and its potential application in metabolites quantification study. Substrates of CES typically undergo a two-step oxygen exchange with H2 18 O in the presence of the enzyme, generating singly- and doubly- 18 O-labeled carboxylic acids; however, unexpected hydrolytic behavior was observed for three of the test compounds – indomethacin, piperacillin and clopidogrel. These unusual observations led to the discovery of several novel hydrolytic mechanisms. Finally, when used as internal standard for LC-MS/MS based quantification, these in situ labeled compounds generated accurate quantitation comparable to the conventional standard curve method. The preliminary results suggest that this method has potential to eliminate laborious chemical synthesis of isotope-labeled internal standards for carboxylic acid-containing compounds, and can be developed to facilitate quantitative analysis in early-stage drug discovery. Graphical abstract: Image 1